Regulation of Transcriptional Coactivator with PDZ-Binding Motif (TAZ) Expression by Estrogen in the Mouse Uterine Endometrium - Hwang, Semi; Kim, Byeongseok; Kim, Johee; Suh, Yeonju; Lee, Jimin; Park, Sangok; Lee, Ok-Hee; Lee, ManRyeol; Choi, Youngsok (Balsaeng'gwa saengsig, 2025)
Transcriptional coactivator with PDZ-binding motif (TAZ) functions as a transcriptional coactivator, which shuttles between the cytoplasm and the nucleus under the Hippo signaling. It is known to be involved in promoting cell proliferation, organ overgrowth, survival to stress, and dedifferentiation by interacting with TEAD transcription factors (TEADs). However, the regulation of TAZ by intrauterine hormones has not yet been investigated. In this study, we investigated TAZ expression during the estrous cycle in the normal mouse uterus and the effect of estrogen and progesterone on TAZ expression in the ovariectomized (OVX) mouse uterus. TAZ expression levels did not show a statistically significant change in the uterus during the estrous cycle. However, immunofluorescence revealed that TAZ nuclear localization significantly increased at the estrus stage. In the OVX mouse uterus, the expression levels of TAZ mRNA and protein dramatically increased in a time-dependent manner after estrogen treatment. Also, immunofluorescence showed that the nuclear TAZ expression increased at 6 h and 12 h after estrogen treatment compared to the oil treated OVX mouse uterus (0 h). Finally, pretreatment of an estrogen receptor (ER) antagonist ICI 182,780 efficiently reduced estrogen-induced TAZ expression. However, progesterone did not significantly affect the expression of TAZ in both mRNA and protein levels. In conclusion, TAZ expression is regulated and activated by estrogen through nuclear estrogen receptors, ERα, and ERβ in the uterine environment.